As velhas novas casas de Usher - Salles, Juliana Rodrigues; Lima, Mirella Márcia Longo Vieira (A Cor das Letras, 2019)
Edgard Allan Poe, writing a short story titled The Fall of the House of Usher in 1839, brought the story of two brothers, the last descendants of a noble lineage, of an ancient and illustrious but decaying family who succumb along with the mansion. who inhabit. This work has points in common with Os Maias, by Eça de Queirós and also with The Chronicle of the Murdered House, by Lucio Cardoso in many ways, from some points in the plot to the description of the houses and their anthropomorphisms. In analyzing passages from the works, we see that Eça de Queirós and Lúcio Cardoso have inspiration from Gothic literature to describe parts of the houses in which the plots appear, creating an atmosphere of decay and finitude.